2005
DOI: 10.26719/2005.11.3.505
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection among pregnant women in Al-Mukalla district, Yemen

Abstract: Urinary tract infection [UTI] is a common problem in pregnant woman. This study examined the frequency of UTI in 137 pregnant women attending Al Mukalla maternity hospital from January to June 2002. Urine samples were examined for UTI microscopically and by culture, and sensitivity tests were done for the organisms isolated using a range of antibiotics. Information on age, trimester, parity and number of pregnancies were also collected for each woman. This study showed that 30% of the women suffered from UTI; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 17 publications
5
9
1
Order By: Relevance
“…The results in this study correspond with the results obtained in Baghdad in which the age group 21-30 had the highest occurrence of UTI pathogens and those ages of 41-50 recorded the lowest incidence (Ghaima et al, 2018). Similar results were also obtained in Yemen in which the age group of 15-24 recorded an incidence of 53.7% (Al Haddad, 2005). However, the study by Amiri et al (2015) revealed that the highest incidence was observed in women above 30 years while the lowest incidence was in the age group of 25-30 years.…”
Section: Discussionsupporting
confidence: 90%
“…The results in this study correspond with the results obtained in Baghdad in which the age group 21-30 had the highest occurrence of UTI pathogens and those ages of 41-50 recorded the lowest incidence (Ghaima et al, 2018). Similar results were also obtained in Yemen in which the age group of 15-24 recorded an incidence of 53.7% (Al Haddad, 2005). However, the study by Amiri et al (2015) revealed that the highest incidence was observed in women above 30 years while the lowest incidence was in the age group of 25-30 years.…”
Section: Discussionsupporting
confidence: 90%
“…11,35,36 In this study, the overall prevalence of urinary tract infections in pregnant women attending hospitals and clinics in Damt City was 60%. The prevalence of UTI 210/350 (60%) in this study was higher than the study conducted in the Al-Mukalla district, Yemen at 30%, 23 Eastern Ethiopia at 13.2%, 37 Bangladesh at 8.9%, 9 Southeast Ethiopia 26%, 38 Iran 17%, 39 and Sudan 12.1%. 40 However, this value was similar to the prevalence of UTI among pregnant women in Taiz Governorate, Yemen, at 58%.…”
Section: Discussioncontrasting
confidence: 73%
“…Haider et al reported the prevalence of ASB during pregnancy is 4.3% followed by another study with incidence rate of 4.8% 23,24 . Some studies in disagreement of the conclusion showed a higher incidence rate of 30% and 40% of ASB in pregnant women 25,26 .…”
Section: Discussionmentioning
confidence: 92%